PENGARUH METODE PROYEK TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI PAUD AT-TAMIMI, KECAMATAN TAMPAN KOTA PEKANBARU - Fedila Elfiga; Ria Novianti; febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the fine motor skills of the students have not developed optimally. So that should be the implematation of project methods. This study aims to determine the effect of applying the methods of the project on the fine motor skills of children aged 5-6 years in early childhood At-Tamimi Handsome District of the city of pekanbaru. The sample used in this study 18 the protege. The data collection techniques were used that observation and documentation. Data were analyzed using t-test using SPSS 18.0. the study hypothesis is the aplication of project methods have an influence on the development of fine motor skills of children aged 5-6 years in early chilhood At-Tamimi Handsome District of the city of Pekanbaru. It can be seen from the analysis of data obtained t = 15 421 and Sig. (2-tailed) = 0,000. Because Sig. (2-tailed) <0.05, it can be concluded that there are differences in the fine motor skills of the students significantly after using project methods in teaching. So it means hHo rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying the method of the project. The effect of applying the method of the project on the fine motor skills of children aged 5-6 years in early childhood At-Tamimi Handsome District of Pekanbaru city by 42.00%. Key Words : Fine Motor Skill, Project Method